Pengaruh Motivasi Dan Perhatian Orang Tua Terhadap Prestasi Mahasiswa Ilmu Al-Qur’An Tafsir : (Studi Kasus di IAI TABAH Lamongan) - Feni Tamimul Ummah; Mayali Maghfiroh; Shofwatul Fikhriyah; Vika Madinatul Ilmi; Alya Khoironi Muhibbah; Dini Maulidah; Faziadatun Ni’mah; Eny Lathifah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
The purpose of this study was to determine whether or not there is an effect of motivation and parental attention on the achievement of Semester 1-7 IAT IAI TABAH students. This research method is Quantitative with the type of case study by maximising Questionnaire, Interview, Observation, and Documentation instruments. The results showed that the influence of motivation and parental attention on achievement for students of Al-Quran Science and Tafsir of the Tarbiyatut Tholabah Lamongan Islamic Institute had no significant effect. 58.8% of parents never demand children to be able to everything.64.7% of parents always support children in campus. 41.2% of parents always support children to buy learning books in campus.70.6% of students rarely buy books. 41.2% of parents never encourage students to go to campus regularly. IAT IAI TABAH student achievement The highest value of Student GPA is 3.68 and the average value is 3.55, while the lowest value is 3.01. From the existing Student Study Result Card data, the highest student value is only able to achieve 3.68 GPA among all students.